The Clarity and Validity of the Concept of Psychological Contract (International Journal of Scientific Research and Management (IJSRM), 2017)
Researchers have argued that the construct of psychological contract in its current form and application lacks clarity and validity. However the debate has stagnated but the research has continued being carried out without considering the diverging views on the subject. This article aims at bridging the gap on the operational definition of the construct, the content of the contract relevant for workplace and the influence on attitudes and behavior. This is articulated through knowledge blending of the theories of law, linguistic and social psychology. The foundation of the construct stems from the assumption that for two parties to draw maximum benefits from their relationship they have to develop commitment and cooperation. The process begins when the party processing the power and effect undertakes to satisfy the needs or interest of the referent other who in turn reciprocate with increased trust and loyalty. In a relationship the psychological contract is the feelings or beliefs held by one party that the other party has adopted to satisfy their need/desire/interest/goal. The content of psychological contract is based on workplace needs frame around Hertzberg two factor to correspond with the different types of equity sensitivity predispositions. This article seeks to theoretically present clarity to the construct of psychological contract in a coherent manner that joins together the current two schools of thought namely classical and reliance (two parties).